Trisomy 21: A Multidisciplinary Perspective: Trissomia 21: Uma Perspetiva Multidisciplinar - Adrião, Mariana; Maia, Ana; Magalhães, Augusto; Moura, Carla; Alegrete, Nuno; Casimiro de Andrade, David; Correia, Cíntia; Rebelo, Joana; Tavares, Marta; Gonçalves, Edite; Guardiano, Micaela (Gazeta Médica, 2019)
INTRODUCTION: Trisomy 21 (T21) is the most common chromosomopathy worldwide, regardless of gender, ethnic group and social class. The newborns typically present with phenotypic characteristics and might have congenital malformations. Our objectives were to create a revision article both accessible and adjusted to the pediatrician’s clinical practice to follow T21 in paediatrics, within a holistic vision of health care. METHODOLOGY: Research of published articles on different areas related to T21 management, including guidelines of numerous pediatrics’ associations. Physicians with experience on the management of patients with T21 on distinct medical specialities contributed to review the literature. CONCLUSION: Through a holistic evaluation and intervention, it is possible to keep improving the clinical care of the pediatric population with T21. Its outcome reflects not only through increase of average life expectancy, but also in the improvement of the quality of life experienced in all age groups.